2020
DOI: 10.3389/fphar.2020.00398
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Multifaceted Antimicrobial Stewardship Intervention in a Primary Health Care Area: A Quasi-Experimental Study

Abstract: The aim of the study was to evaluate the impact of a multifaceted antimicrobial stewardship intervention on antibiotic consumption in a primary health care (PHC) area in Spain. Quasi-experimental study conducted in a PHC area with nine PHC centers, a 400-bed acute care teaching hospital, and 18 nursing homes serving a population of 260,561. The intervention was based on the 2016 CDC Core Elements of Outpatient Antibiotic Stewardship publication and targeted 130 PHC physicians, 41 PHC pediatricians, 19 emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(51 citation statements)
references
References 24 publications
1
49
0
Order By: Relevance
“…The most common diseases were respiratory tract infections (RTIs) [ 39 , 51 , 53 , 55 , 56 , 61 , 62 , 63 , 66 ], and either upper-RTIs (URTI) [ 39 , 55 , 61 , 62 , 63 ] or lower-RTIs (LRTIs) [ 51 ]. Most studies included patients from all age groups [ 2 , 39 , 43 , 44 , 45 , 48 , 50 , 56 , 57 , 58 , 59 , 60 , 65 , 66 , 67 , 68 ], only five included adults [ 47 , 49 , 51 , 52 , 55 ], four children [ 53 , 61 , 62 , 63 ] and two older adults [ 38 , 40 , 41 , 42 , 46 , 54 , 64 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common diseases were respiratory tract infections (RTIs) [ 39 , 51 , 53 , 55 , 56 , 61 , 62 , 63 , 66 ], and either upper-RTIs (URTI) [ 39 , 55 , 61 , 62 , 63 ] or lower-RTIs (LRTIs) [ 51 ]. Most studies included patients from all age groups [ 2 , 39 , 43 , 44 , 45 , 48 , 50 , 56 , 57 , 58 , 59 , 60 , 65 , 66 , 67 , 68 ], only five included adults [ 47 , 49 , 51 , 52 , 55 ], four children [ 53 , 61 , 62 , 63 ] and two older adults [ 38 , 40 , 41 , 42 , 46 , 54 , 64 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The educational interventions implementation period ranged from 14 days [ 53 ] to 8 years [ 45 ]. Some studies compared similar periods of different years [ 2 , 38 , 39 , 40 , 42 , 43 , 44 , 49 , 52 , 53 , 59 , 60 , 64 , 65 , 66 , 67 , 68 , 69 ], within the same year [ 63 ] or both situations [ 41 , 50 , 57 , 62 ]. Only eleven studies [ 39 , 42 , 52 , 53 , 56 , 57 , 58 , 59 , 62 , 66 , 69 ] performed a follow-up analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicated that, in 2017, Chinese primary healthcare clinicians prescribed antibiotics for nearly half of outpatients with acute bronchitis, which was a lower rate than those in the studies conducted in Italy (73.5%) 13 , US (74%) 14 , Belgium (69.0%) 15 , Spain (58.6%) 16 , Japan (52.8%) 17 , and Netherlands (51.0%) 18 , and was also lower than previous studies in China (77.5–95.2%) 9 , 11 . However, our rate was slightly higher than the rate showed in the study conducted in Swiss (41.5%) 19 .…”
Section: Discussionmentioning
confidence: 56%
“…Although we identify high-priority areas for ambulatory ASPs, it is important to note that successful ASPs are multifaceted, as seen with our survey respondents reporting greater rates of effectiveness as more CDC Core Elements of Outpatient Antimicrobial Stewardship are met [ 16 , 25 , 26 ]. Likewise, March-López et al [ 25 ] report that a multilayered outpatient study using interventions in line with the CDC Core Elements resulted in a 17% reduction in overall antibiotic utilization. A key component of this success was dependent on the personnel support provided to the ASP.…”
Section: Discussionmentioning
confidence: 99%